2021
DOI: 10.1016/j.heliyon.2021.e07898
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like protein 4 (ANGPTL4) is an inhibitor of endothelial lipase (EL) while the ANGPTL4/8 complex has reduced EL-inhibitory activity

Abstract: We previously demonstrated that angiopoietin-like protein 8 (ANGPTL8) forms ANGPTL3/8 and ANGPTL4/8 complexes that increase with feeding to direct fatty acids (FA) toward adipose tissue through differential modulation of lipoprotein lipase (LPL) activity. Each complex correlated inversely with high density lipoprotein cholesterol (HDL) in control subjects. We thus investigated ANGPTL3/8 and ANGPTL4/8 levels in type 2 diabetes patients, who can present with decreased HDL. While ANGPTL3/8 levels in type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 30 publications
1
27
1
Order By: Relevance
“…In light of our recent observations that ANGPTL3/8 can also inhibit EL activity and do so more potently than ANGPTL3 alone ( 62 ), we performed additional experiments to determine the effect of the anti-ANGPTL3/8 antibody and evinacumab on ANGPTL3/8-mediated inhibition of EL. Interestingly, we observed that the anti-ANGPTL3/8 antibody and evinacumab both comparably blocked ANGPTL3/8-mediated EL inhibition and did so much less completely and potently (IC 50 values of 53 nM and 78 nM, respectively) than they blocked ANGPTL3/8-mediated LPL inhibition ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of our recent observations that ANGPTL3/8 can also inhibit EL activity and do so more potently than ANGPTL3 alone ( 62 ), we performed additional experiments to determine the effect of the anti-ANGPTL3/8 antibody and evinacumab on ANGPTL3/8-mediated inhibition of EL. Interestingly, we observed that the anti-ANGPTL3/8 antibody and evinacumab both comparably blocked ANGPTL3/8-mediated EL inhibition and did so much less completely and potently (IC 50 values of 53 nM and 78 nM, respectively) than they blocked ANGPTL3/8-mediated LPL inhibition ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A human endothelial lipase (EL) activity assay was optimized to allow measurement of the phospholipase A1 activity of EL, which preferentially hydrolyzes phospholipids (PLs) at the sn -1 position and was performed as previously described ( 62 ), with some minor modifications. After overnight incubation of EL-stable expression cells at 37°C, the medium was replaced with 80 μl of medium (OptiMEM, Invitrogen) containing human ANGPTL3/8 complex or human ANGPTL3 at their respective IC 80 concentrations (38 nM or 328 nM) that were each preincubated with increasing concentrations of either the anti-ANGPTL3/8 antibody or evinacumab.…”
Section: Methodsmentioning
confidence: 99%
“…Future studies to identify human SNPs that result in a complete ANGPTL8 deficiency will further confirm the hypothesis of ANGPTL8-antagonism based therapeutics. Future drug development requires a clear mechanistic understanding of how the ANGPTL3-4-8 system works in regulating EL ( 9 , 15 ), as what it does to LPL ( 2 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the hypothesized model ( Figure 1 ) appears to be oversimplified, because it lacks ANGPTL4. The hypothesis holds true, however, whether or not ANGPTL8 increases ANGPTL3's EL-inhibiting activity ( 9 , 15 ), because when ANGPTL3-8 complexes are disrupted, fewer ANGPTL3-8 complexes and more free ANGPTL3 still lead to higher LPL and lower EL activities, respectively.…”
Section: Weaknessesmentioning
confidence: 99%
See 1 more Smart Citation